Direct cardiac reprogramming via combined CRISPRa-mediated endogenous Gata4 activation and exogenous Mef2c and Tbx5 expression - Peisen Huang; Jun Xu; Benjamin Keepers; Yifang Xie; David Near; Yangxi Xu; James Rock Hua; Brian Spurlock; Shea Ricketts; Jiandong Liu; Li Wang; Li Qian (Molecular Therapy: Nucleic Acids)
Direct cardiac reprogramming of fibroblasts into induced cardiomyocytes (iCMs) can be achieved by ectopic expression of cardiac transcription factors (TFs) via viral vectors. However, risks like genomic mutations, viral toxicity, and immune response limited its clinical application. Transactivation of endogenous TFs emerges as an alternative approach that may partially mitigate some of the risks. In this study, we utilized a modified CRISPRa/dCas9 strategy to transactivate endogenous reprogramming factors MEF2C, GATA4, and TBX5 (MGT) to induce iCMs from both mouse and human fibroblasts. We identified single-guide RNAs (sgRNAs) targeting promoters and enhancers of the TFs capable of activating various degrees of endogenous gene expression. CRISPRa-mediated Gata4 activation, combined with exogenous expression of Mef2c and Tbx5, successfully converted fibroblasts into iCMs. Despite extensive sgRNA screening, transactivation of Mef2c and Tbx5 via CRISPRa remained less effective, potentially due to de novo epigenetic barriers. While future work and refined technologies are needed to determine whether cardiac reprogramming could be achieved solely through CRISPRa activation of endogenous factors, our findings provide proof of concept that reliance on exogenous TFs for reprogramming can be reduced through CRISPRa-mediated activation of endogenous factors, particularly Gata4, offering a novel strategy to convert scar-forming fibroblasts into iCMs for regenerative purposes.